A Comparative Analysis of Tellurite Detoxification by Members of the Genus Shewanella - Vasquez-Guzman, C; Ruiz-Leon, D; Ruiz-Leon, D (Springer Verlag, 2018)
The increasing industrial utilization of tellurium has resulted in an important environmental pollution with the soluble, extremely toxic oxyanion tellurite. In this context, the use of microorganisms for detoxifying tellurite or tellurium biorecovery has gained great interest. The ability of different Shewanella strains to reduce tellurite to elemental tellurium was assessed; the results showed that the reduction process is dependent on electron transport and the ∆pH gradient. While S. baltica OS155 showed the highest tellurite resistance, S. putrefaciens was the most efficient in reducing tellurite. Moreover, pH-dependent tellurite transformation was associated with tellurium precipitation as tellurium dioxide. In summary, this work highlights the high tellurite reduction/detoxification ability exhibited by a number of Shewanella species, which could represent the starting point to develop friendly methods for the recovery of elemental tellurium (or tellurium dioxide). © 2017, Springer-Verlag GmbH Germany.